2020
DOI: 10.1016/j.cmi.2020.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostic accuracies of rapid serological tests and ELISA to molecular diagnostics in patients with suspected coronavirus disease 2019 presenting to the hospital

Abstract: Objectives: To assess the diagnostic performance of rapid lateral flow immunochromatographic assays (LFAs) compared with an ELISA and nucleic acid amplification tests (NATs) in individuals with suspected coronavirus disease 2019 . Methods: Patients presenting to a Dutch teaching hospital were eligible between 17 March and 10 April 2020, when they had respiratory symptoms that were suspected for COVID-19. The performances of six different LFAs were evaluated in plasma samples obtained on corresponding respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 10 publications
4
90
0
1
Order By: Relevance
“…Numerous studies have surveyed the clinical performance of specific SARS-CoV-2 serology assays to date, many of which are compiled elsewhere [ 15 , 23 , 78 , 96 , 117 , 142 , 151 , [158] , [159] , [160] , [161] , [162] ]. Some of these tests indicated an insufficient diagnostic reliability for patient testing while others demonstrated clinically solid performance.…”
Section: Clinical Performance and Utility Of Serology Assays For Sarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have surveyed the clinical performance of specific SARS-CoV-2 serology assays to date, many of which are compiled elsewhere [ 15 , 23 , 78 , 96 , 117 , 142 , 151 , [158] , [159] , [160] , [161] , [162] ]. Some of these tests indicated an insufficient diagnostic reliability for patient testing while others demonstrated clinically solid performance.…”
Section: Clinical Performance and Utility Of Serology Assays For Sarsmentioning
confidence: 99%
“…Some of these tests indicated an insufficient diagnostic reliability for patient testing while others demonstrated clinically solid performance. ELISA and chemiluminescence immunoassays tended to yield improved diagnostic sensitivities in various surveys versus LFAs, with the latter showing moderate rates of both false positives and false negatives in studies using multiple LFAs [ 96 , 99 , 161 , 162 ]. The majority of the assays voluntarily withdrawn or not issued an EUA were LFAs [ 151 ].…”
Section: Clinical Performance and Utility Of Serology Assays For Sarsmentioning
confidence: 99%
“…Since the start of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak in December 2019 in Wuhan, China, the virus has rapidly spread and become a major public health concern all over the world ( Van Elslande et al, 2020 , Ong et al, 2020 ). As of July 1, 2020, the virus has caused more than 10 million confirmed infections and over 500,000 reported deaths ( Organization, W.H., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specific antibodies against SARS-CoV-2 can be detected as early as 4-7 days in approximately 40% of COVID-19 patients, with seroconversion rates reaching more than 90% by day 14 ( Zhao et al, 2020 ). Therefore, serology could be used as a complementary test to RT-PCR to improve the diagnostic sensitivity, particularly in suspected COVID-19 individuals with negative RT-PCR results or those with no respiratory sample collected during the acute phase of illness ( Van Elslande et al, 2020 , Ong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Further, in a study comparing six commercial rapid LFAs to an ELISA for COVID-19 serology testing, the ELISA outperformed all six LFAs for clinical sensitivity and specificity. 12 In that study the most sensitive LFA reported a sensitivity of 60% while the ELISA reported 79% sensitivity for the same samples. LFAs will inherently perform more poorly than ELISAs for two reasons: 1) They cannot wash excess reagent and/or sample from the detection zone to mitigate non-specific adsorption, and 2) nanoparticle labels cannot amplify colorimetric signal like enzymatic reporters.…”
Section: Introductionmentioning
confidence: 83%